Endovascular treatment of popliteal artery aneurysm. Early and midterm results - Domingues,Rodrigo Borges (2015)
OBJECTIVE: to evaluate the efficacy of endovascular repair of popliteal artery aneurysms on maintaining patency of the stent in the short and medium term. METHODS: this was a retrospective, descriptive and analytical study, conducted at the Integrated Vascular Surgery Service at the Hospital da Beneficência Portuguesa de São Paulo. We followed-up 15 patients with popliteal aneurysm, totaling 18 limbs, treated with stent from May 2008 to December 2012. RESULTS: the mean follow-up was 14.8 months. During this period, 61.1% of the stents were patent. The average aneurysm diameter was 2.5cm, ranging from 1.1 to 4.5cm. The average length was 5cm, ranging from 1.5 to 10 cm. In eight cases (47.1%), the lesion crossed the joint line, and in four of these occlusion of the prosthesis occurred. In 66.7% of cases, treatment was elective and only 33.3% were symptomatic patients treated on an emergency basis. The stents used were Viabahn (Gore) in 12 cases (66.7%), Fluency (Bard) in three cases (16.7%), Multilayer (Cardiatis) in two cases (11.1%) and Hemobahn (Gore) in one case (5.6%). In three cases, there was early occlusion (16.6%). During follow-up, 88.2% of patients maintained antiplatelet therapy. There was no leakage at ultrasound (endoleak). No fracture was observed in the stents. CONCLUSION: the results of this study are similar to other published series. Probably, with the development of new devices that support the mechanical characteristics found on the thighs, there will be improved performance and prognosis of endovascular restoration.